Six Feet Under : Complete Fourth Series Disc 3 Episode 6-8 - Ball, Alan.; Krause, Peter (USA HBO Home Video, 2004)
A drama series that takes a darkly comical look at members of a dysfunctional Pasadena family that runs an independent funeral home. With the prodigal elder son (Peter Krause) returning home for the holidays to shattering news, the family must learn to deal with a death of their own, while figuring out how to go ahead with the business of the living. A funny and emotional look at a grieving American family...that just happens to be in the grief management business.
Nathaniel Fisher, his wife Ruth, and their children David and Claire run a small funeral business that offers the best care to be found anywhere close by. Prodigal son Nate Jr. arrives home for Christmas just as his father is killed by a bus, and has to stick around when he and David are willed the funeral service together. How does a family who helps others deal with grief deal with its own?
Every Day Above Ground Is A Good One.
Languages : English, French, Hungarian
Subtitles : English, French, Hungarian, Dutch, Arabic, Finnish, Greek, Hebrew, Norwegian, Polish, Swedish
Keywords: Comedy -- TV Series; Drama